2019
DOI: 10.1097/fjc.0000000000000642
|View full text |Cite
|
Sign up to set email alerts
|

LongShengZhi Capsule Reduces Established Atherosclerotic Lesions in apoE-Deficient Mice by Ameliorating Hepatic Lipid Metabolism and Inhibiting Inflammation

Abstract: Disorders of lipid metabolism and inflammation play an important role in atherosclerosis. LongShengZhi (LSZ) capsule, a Chinese herbal medicine, has been used for treatment of patients with vascular diseases for many years. In this article, we determined the effect of LSZ on the progression of established atherosclerotic lesions in apoE-deficient (apoE−/−) mice. ApoE−/− mice were prefed high-fat diet (HFD) for 8 weeks to induce atherosclerosis, then started with LSZ treatment contained in HFD for 10 weeks. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…LongShengZhi Capsule as a traditional Chinese medicine for treatment of atherosclerotic cerebral infarction is usually used to treat hemiplegia and stroke caused by atherosclerosis with a high degree of safety. In our previous study, we showed LSZ has few side effects (Li et al, 2019;Ma et al, 2019;Xu et al, 2020). Similarly, in this study, we treated the animal with LSZ for 7 months and found no difference in bodyweight gain, food intake, and the external appearance between control and LSZ-treated groups, which further confirms the high degree of safety of the long-term LSZ treatment.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…LongShengZhi Capsule as a traditional Chinese medicine for treatment of atherosclerotic cerebral infarction is usually used to treat hemiplegia and stroke caused by atherosclerosis with a high degree of safety. In our previous study, we showed LSZ has few side effects (Li et al, 2019;Ma et al, 2019;Xu et al, 2020). Similarly, in this study, we treated the animal with LSZ for 7 months and found no difference in bodyweight gain, food intake, and the external appearance between control and LSZ-treated groups, which further confirms the high degree of safety of the long-term LSZ treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Our previous studies have shown that LSZ can reduce thrombosis by inhibiting platelet adhesion through reducing oxidative stress and vascular inflammation in the aorta of atherosclerotic mice (Li et al, 2019;Ma et al, 2019). Moreover, we have demonstrated its strong antioxidant role in heart failure (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…We previously reported that amelioration of hepatic lipid metabolism is a positive effect to anti-atherosclerosis (32,33). In this study, although TL1A has little effect on hypercholesterolemia in HFD-fed apoE -/mice, it reduced TG accumulation in the liver (Fig.…”
Section: Discussionmentioning
confidence: 50%